2006
DOI: 10.1074/jbc.m511165200
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Affinity Maturation, and Biological Characterization of an Anti-tumor-associated Glycoprotein-72 Humanized Antibody

Abstract: The tumor-associated glycoprotein (TAG)-72 is expressed in the majority of human adenocarcinomas but is rarely expressed in most normal tissues, which makes it a potential target for the diagnosis and therapy of a variety of human cancers. Here we describe the construction, affinity maturation, and biological characterization of an anti-TAG-72 humanized antibody with minimum potential immunogenicity. The humanized antibody was constructed by grafting only the specificity-determining residues (SDRs) within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Such SDR-grafted humanized antibodies resulted in lower immunogenic potential compared to CDR-grafted humanized antibodies. [116][117][118][119] of the antibody. 79 Taking these potential issues into consideration, improving solubility by introducing an N-linked carbohydrate in the variable region might not be a first-line approach for improving the solubility.…”
Section: Reducing the Immunogenicitymentioning
confidence: 99%
“…Such SDR-grafted humanized antibodies resulted in lower immunogenic potential compared to CDR-grafted humanized antibodies. [116][117][118][119] of the antibody. 79 Taking these potential issues into consideration, improving solubility by introducing an N-linked carbohydrate in the variable region might not be a first-line approach for improving the solubility.…”
Section: Reducing the Immunogenicitymentioning
confidence: 99%
“…However, grafting of the six CDRs of murine antibodies onto appropriate frameworks of human antibodies often results in reduced affinity or specificity for the target antigen (10,14,16). The pioneering work of Foote and Winter (21) has suggested that antibody residues in the ␀-sheet framework underlying the CDRs play a critical role in adjustment of the loop structures of the CDRs.…”
mentioning
confidence: 99%
“…The next approach was, therefore, the use of specificity-determining residue (SDR) grafting, in which only the SDRs (not whole CDRs) are grafted onto the germline antibodies. These SDR-grafted humanized antibodies indeed showed lower immunogenicity than CDR-grafted humanized antibodies [379][380][381][382].…”
Section: Humanized Antibodiesmentioning
confidence: 99%